"Not living together yet all the time together": The construction of living apart together in continuing care retirement communities from perspectives of residents and CCRC staff*. (November 2019) - Koren, Chaya; Ayalon, Liat
Moving to a continuing care retirement community (CCRC) and living apart together (LAT) late in life are occurrences representing new beginnings in old age. However, they may also involve restrictions related to partnership characteristics and to the semi-totalitarian features of the CCRC. From community, person-in-environment and person–environment fit/misfit approaches, we aim to examine how LAT relationships are constructed in the CCRC from perspectives of residents and CCRC staff as members of the same semi-totalitarian communities. This could provide new understandings on CCRC features and LAT relationships for enhancing residents' quality-of-life. A total of 30 semi-structured qualitative interviews were conducted in three CCRCs in Israel: 10 with widowed LAT residents, 10 with widowed residents not LAT, and 10 with CCRC staff. The interviews were analyzed based on thematic analysis and triangulated to produce a broad and rich experience of LAT in the CCRC. Two themes that characterize LAT relationships in the CCRC were identified: (1) friendship rather than partnership characterize the LAT relationship and (2) not living together yet being all the time together. The intersection between the social environment (the CCRC) as a semi-totalitarian institution and the persons (residents in LAT and not in LAT and CCRC staff) is discussed. The discussion focuses on LAT relationships in the CCRC as representing exclusive friendship and the limited autonomy associated with not living together yet being all the time together. Implications on micro, mezzo, and macro levels are suggested.